A grape breeding programme using different Vitis species. (4th October 2021) - Atak, Arif; Şen, Abdulbaki
Abstract: Intensive breeding programmes have been carried out to obtain high‐quality seedless grape cultivars. Seedless grape cultivars were used as pollinizer parents, but the number of hybrid seeds and the viability of the seed obtained could differ greatly. In this study, carried out over 3 years, the results obtained from crossing with some pollinizer cultivars belonging to different Vitis species were compared. Maternal cultivars that do not need emasculation (male sterile) and emasculated cultivars were also compared. Evaluations were based on the total number of hybrid seeds and the proportion of viable seeds. In addition, the effects of various treatments on the rates of germination of the hybrid seed were compared. Although the female parents (with female flower structure) produced more seed than did hermaphrodite mothers in 2019, different results were obtained in cross‐breeding studies in 2018 and 2020. Cold stratification was very effective in increasing germination by breaking dormancy of the hybrid seed. In addition, after treatment of cold moist storage (cold stratification), keeping the seed in distilled water overnight before planting increased germination. Although large numbers of seeds were produced by the genotype 86/1 and the cultivar 'Beyaz Çavuş', both of which do not require emasculation, many of these seeds did not germinate. Crosses with the cultivar 'Red Globe' as the maternal parent produced large numbers of viable seeds and high germination rates.